GALACTIC NONLINEAR DYNAMIC MODEL - De Melo, C. A. M. [UNESP]; Resende, S. T. (World Scientific Publ Co Pte Ltd, 2009)
We develop a model for spiral galaxies based on a nonlinear realization of the Newtonian dynamics starting from the momentum and mass conservations in the phase space. The radial solution exhibits a rotation curve in qualitative accordance with the observational data.
Keywords: Galactic rotation curves; dark matter; mathematical modeling